Differences in socioeconomic and gender inequalities in tobacco smoking in Denmark and Sweden; a cross sectional comparison of the equity effect of different public health policies - Andersen Ingelise; Rasmussen Niels K; Diderichsen Finn; Östergren Per-Olof; Eek Frida; Moussa Kontie; Grahn Mathias (BMC, 2010)
Abstract Background Denmark and Sweden are considered to be countries of rather similar socio-political type, but public health policies and smoking habits differ considerably between the two neighbours. A study comparing mechanisms behind socioeconomic inequalities in tobacco smoking, could yield information regarding the impact of health policy and -promotion in the two countries. Methods Cross-sectional comparisons of socioeconomic and gender differences in smoking behaviour among 6 995 Danish and 13 604 Swedish persons aged 18-80 years. Results The prevalence of smoking was higher in Denmark compared to Sweden. The total attributable fraction (TAF) of low education regarding daily smoking was 36% for Danish men and 35% for Danish women, and 32% and 46%, respectively, for Swedish men and women. TAF of low education regarding continued smoking were 16.2% and 15.8% for Danish men and women, and 11.0% and 18.8% for Swedish men and women, respectively The main finding of the study was that the socioeconomic patterning of smoking, based on level of education and expressed as the relative contribution to the total burden of smoking exposure, was rather different in Sweden and Denmark. Moreover, these differences were modified by gender and age. As a general pattern, socioeconomic differences in Sweden tended to contribute more to the total burden of this habit among women, especially in the younger age groups. In men, the patterns were much more similar between the two countries. Regarding continued smoking/unsuccessful quitting, the patterns were similar for women, but somewhat different for men. Here we found that socioeconomic differences contributed more to overall continued smoking in Danish men, especially in the middle-age and older age strata. Conclusion The results imply that Swedish anti-smoking policy and/or implemented measures have been less effective in a health equity perspective among the younger generation of women, but more effective among men, compared to Danish policy implementation. The results also raises the more general issue regarding the possible need for a trade-off principle between overall population efficacy versus equity efficacy of anti-tobacco, as well as general public health policies and intervention strategies.